Unexpected Phenotype Reversion and Survival in a Zebrafish Model of Multiple Sulfatase Deficiency - Fleming, Angeleen; Xuan, Low Zhe; Sanchez-Elexpuru, Gentzane; Williams, Sarah V.; Windell, Dylan; Gelb, Michael H.; Herbst, Zackary M.; Schlotawa, Lars; Rubinsztein, David C. (Frontiers in Cell and Developmental Biology, 2022)
Multiple sulfatase deficiency (MSD) is a rare recessively inherited Mendelian disorder that manifests with developmental delay, neurodegeneration, skeletal deformities, facial dysmorphism, congenital growth retardation and other clinical signs. The disorder is caused by mutations in the SUMF1 gene, which encodes the formylglycine-generating enzyme (FGE), responsible for the activation of sulfatases. Mutations in SUMF1 result in reduced or absent FGE function with consequent compromised activities of its client sulfatases. This leads to an accumulation of enzyme substrates, such as glycosaminoglycans and sulfolipids, within lysosomes that are associated with impaired lysosome function and cellular pathology. Currently, there are no disease modifying therapeutic options for MSD patients, hence the need for more suitable animal models to investigate the disorder. Here, we describe the characterisation of a sumf1 null zebrafish model, which has negligible sulfatase activity. Our sumf1-/- zebrafish model successfully recapitulates the pathology of MSD such as cranial malformation, altered bone development, an enlarged population of microglia, and growth retardation during early development but lacks early lethality of mouse Sumf1-/- models. Notably, we provide evidence of recovery in MSD pathology during later developmental stages, resulting in homozygous mutants that are viable. Hence, our data suggest the possibility of a unique compensatory mechanism that allows the sumf1-/- null zebrafish to survive better than human MSD patients and mouse Sumf1-/- models.